2020
DOI: 10.1017/jfm.2020.839
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of shear-layer coherent structures in a forced wall-bounded flow

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…This is also in line with recent studies of the effect of streaks on the KH instability mechanism (Marant & Cossu 2018; Lajús et al. 2019; Nogueira & Cavalieri 2021), which have shown that such elongated structures can have a stabilising/destabilising effect on the KH mode. Figure 7( c ) shows the phase portrait of modes 1 and 2, for restricted values of ().…”
Section: Resultssupporting
confidence: 91%
“…This is also in line with recent studies of the effect of streaks on the KH instability mechanism (Marant & Cossu 2018; Lajús et al. 2019; Nogueira & Cavalieri 2021), which have shown that such elongated structures can have a stabilising/destabilising effect on the KH mode. Figure 7( c ) shows the phase portrait of modes 1 and 2, for restricted values of ().…”
Section: Resultssupporting
confidence: 91%
“…Considering that the introduction of streaks in the flow can affect the growth rate of the KH mode (Marant & Cossu 2018; Lajús et al. 2019; Nogueira & Cavalieri 2021), these previous results can actually be connected to a mitigation of the absolute instability presented herein. This is a simple example of how the present analysis can be applied to experiments and engineering applications.…”
Section: Discussionsupporting
confidence: 51%
“…The above studies offer insight into nonlinear interactions among wavepackets, with results that depend on the details of upstream excitation, a natural feature of shear layers and jets. In Nogueira & Cavalieri (2021) (hereafter referred to as NC) we have adopted a different strategy and circumvented the upstream excitation problem by defining a shear layer that is homogeneous in the streamwise direction; this is accomplished by considering a shear layer driven by a body force and confined by two horizontal walls, as sketched in…”
Section: Introductionmentioning
confidence: 99%